Combined Coronary Artery Bypass Grafting and Open Abdominal Aortic Aneurysm Repair Is a Reasonable Treatment Approach: A Systematic Review. (August 2014) - Spanos, Konstantinos; Saleptsis, Vasileios; Karathanos, Christos; Rousas, Nikolaos; Athanasoulas, Athanasios; Giannoukas, Athanasios D.
We reviewed the literature for studies investigating the outcomes of combined 1-stage coronary artery bypass grafting (CABG) and abdominal aortic aneurysm (AAA) open repair (OR) procedures. An electronic search of the English literature was conducted using the PubMed, EMBASE, and Cochrane databases. Age, coronary heart disease severity, AAA size, mean duration from CABG to AAA OR procedures, details of each procedure, mortality, and morbidity rates were analyzed. Between 1994 and 2012, 12 studies (256 patients) with 1-stage treatment fulfilled the inclusion criteria and were analyzed. There were 20 early (30 days) deaths, accounting for a 30-day mortality rate of 7.8%. The early morbidity was 53% (136 of 256). One-stage treatment when necessary can be undertaken with acceptable mortality and reasonable morbidity rates considering the complexity of both the operations. Nowadays, endovascular AAA repair is preferred over OR. The outcomes of combined cardiac surgery and endovascular AAA repair have not been extensively evaluated.